Biological phosphorus removal in seawater-adapted aerobic granular sludge. (1st April 2020) - de Graaff, Danny R.; van Loosdrecht, Mark C.M.; Pronk, Mario
Abstract: Seawater can be introduced or intrude in sewer systems and can thereby negatively influence biological wastewater treatment processes. Here we studied the impact of artificial seawater on the enhanced biological phosphate removal (EBPR) process performance by aerobic granular sludge (AGS) with synthetic wastewater. Process performance, granule stability and characteristics as well as microbial community of a seawater-adapted AGS system were observed. In seawater conditions strong and stable granules formed with an SVI5 of 20 mL/g and a lower abrasion coefficient than freshwater-adapted granules. Complete anaerobic uptake of acetate, anaerobic phosphate release of 59.5 ± 4.0 mg/L PO4 3- -P (0.35 mg P/mg HAc), and an aerobic P-uptake rate of 3.1 ± 0.2 mg P/g VSS/h were achieved. The dominant phosphate accumulating organisms (PAO) were the same as for freshwater-based aerobic granular sludge systems with a very high enrichment of Ca. Accumulibacter phosphatis clade I, and complete absence of glycogen accumulating organisms. The effect of osmotic downshocks was tested by replacing influent seawater-based medium by demineralized water-based medium. A temporary decrease of the salinity in the reactor led to a decreased phosphate removal activity, while it also induced a rapid release of COD by the sludge, up to 45.5 ± 1.7 mg COD/g VSS. This is most likely attributed to the release of osmolytes by the cells. Recovery of activity was immediately after restoring the seawater feeding. This work shows that functioning of aerobic granular sludge in seawater conditions is as stable as in freshwater conditions, while past research has shown a negative effect on operation of AGS processes with NaCl-based wastewater at the same salinity as seawater. Highlights: Biological phosphorus removal was achieved with aerobic granular sludge in seawater. Ca. Accumulibacter clade I was present in seawater-adapted aerobic granular sludge. Anaerobic acetate uptake recovered immediately after a single osmotic downshock. Seawater-adapted granules consume acetate as rapidly in seawater as in freshwater. Osmotic downshocks give rapid release of COD, which is likely due to osmolytes.